Quercetin and Glioma: Which Signaling Pathways are Involved? - Tamtaji, Omid R.; Razavi, Zahra Sadat; Razzaghi, Nazanin; Aschner, Michael; Barati, Erfaneh; Mirzaei, Hamed (Current Molecular Pharmacology, 2022)
Gliomas are the most common brain tumors. These tumors commonly exhibit continuous growth without invading surrounding brain tissues. Dominant remedial approaches suffer limited therapy and survival rates. Although some progress has been made in conventional glioma treatments, these breakthroughs have not yet proven sufficient for treating this malignancy. The remedial options are limited given gliomas' aggressive metastasis and drug resistance. Quercetin, a flavonoid, is an anti-oxidative, anti-allergic, antiviral, anti-inflammatory, and anticancer compound. Multiple lines of evidence have shown that Quercetin has anti-tumor effects, documenting this natural compound exerts its pharmacological effects by targeting a variety of cellular and molecular processes, i.e., apoptosis, metastasis, and autophagy. Herein, we summarize various cellular and molecular pathways that are affected by Quercetin in gliomas.
Keywords: apoptosis